2014
DOI: 10.1016/j.jpainsymman.2013.07.014
|View full text |Cite
|
Sign up to set email alerts
|

Supportive Cryotherapy: A Review From Head to Toe

Abstract: Context Conventional chemotherapy leads to multiple adverse mucocutaneous complications including oral mucositis, alopecia, ocular toxicity, and onycholysis. Limited pharmacologic interventions are available for preventing these clinical problems. Objectives This study aimed to critically review the role of cryotherapy (regional hypothermia) for alleviating these adverse symptoms. Methods A narrative review was performed, with an emphasis on randomized controlled trials. A comprehensive search using PubMed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(36 citation statements)
references
References 100 publications
1
32
0
3
Order By: Relevance
“…New research shows a growing interest towards cryotherapy or regional hypothermia for alleviating chemotherapyinduced toxicities such as oral mucositis, ocular toxicity, onycholysis and peripheral neuropathy [11]. Of these debilitating side effects, chemotherapy-induced peripheral neuropathy (CIPN) is a common dose-limiting toxicity of several neurotoxic chemotherapeutic agents, manifesting as severe pain and tingling sensation in the finger and toe tips [30].…”
Section: Introductionmentioning
confidence: 99%
“…New research shows a growing interest towards cryotherapy or regional hypothermia for alleviating chemotherapyinduced toxicities such as oral mucositis, ocular toxicity, onycholysis and peripheral neuropathy [11]. Of these debilitating side effects, chemotherapy-induced peripheral neuropathy (CIPN) is a common dose-limiting toxicity of several neurotoxic chemotherapeutic agents, manifesting as severe pain and tingling sensation in the finger and toe tips [30].…”
Section: Introductionmentioning
confidence: 99%
“…The first of these trials (Mahood et al, 1991) found that the use of oral cryotherapy during infusion of bolus 5-fluorouracil reduced the incidence of mucositis by about 50%. Several confirmatory analyses followed, and similar results were produced (Kadakia et al, 2014).…”
Section: Oral Cryotherapy In the Literaturementioning
confidence: 61%
“…Oral cryotherapy is a technique that has been studied extensively since the 1990s, with the intention of preventing or reducing the severity of mucositis during chemotherapy infusion (Peterson et al, 2013). The cooling of the oral mucous membranes with ice chips causes hypothermic vasoconstriction of blood vessels in the buccal membrane, which limits the exposure of cytotoxins to the mucosa (Kadakia, Rozell, Butala, & Loprinzi, 2014). For best results, the patient should begin to hold ice in his or her mouth at least 5-15 minutes prior to the start of the infusion.…”
Section: Mucositis Prevention and Oral Cryotherapymentioning
confidence: 99%
“…However, it is only effective for short bolus chemotherapeutic infusions [38], may not be tolerated by some subjects, and thus cannot play a significant role in radiation-induced oral mucositis treatments [25]. …”
Section: Mucositis Managementmentioning
confidence: 99%